Positive electrode material of lithium ion capacitor, preparation method of positive electrode material and lithium ion capacitor adopting positive electrode material
High-capacity spherical porous activated carbon material was directly prepared from the concentrated papermaking black liquid by spray pyrolysis, which solved the problems of pollution and low resource utilization in the prior art treatment of papermaking black liquid, and achieved efficient preparation of lithium-ion capacitor positive electrode materials and improved capacitor performance.
Patent Information
- Application Number
- CN202411873180.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The prior art has problems such as high pollution, low resource utilization, complex operation and long process when dealing with papermaking black liquid, making it difficult to efficiently prepare high-capacity activated carbon materials for cathode materials for lithium ion capacitors.
The concentrated papermaking black liquid was directly prepared by spray pyrolysis method to directly prepare spherical porous activated carbon materials, and carbonization and activation were achieved in one step by using the high-temperature pyrolysis and activation of pores, simplifying the process and improving resource utilization.
The efficient value-addedness of papermaking black liquid was achieved, and porous spherical activated carbon material with high capacity characteristics was prepared, which was used as the positive electrode material for lithium-ion capacitors, which improved the energy density and cycle stability of the capacitor.
Smart Images

Figure CN119650312A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitors and positive electrode materials thereof, and in particular to a positive electrode material for a lithium ion capacitor and a preparation method thereof, and a lithium ion capacitor using the positive electrode material. Background Art
[0002] Lithium-ion capacitors or supercapacitors have the characteristics of high power, long cycle life, fast charge and discharge speed, etc. They are unique power-type energy storage devices. Activated carbon materials are the key electrode materials of lithium-ion capacitors or supercapacitors, which significantly affect the performance of the device. Ideal activated carbon materials should have suitable microstructure and morphology, high specific surface area, and reasonable pore size distribution.
[0003] Papermaking black liquor is a dark brown wastewater containing a large amount of lignin produced by the alkaline pulping process, and also contains some hemicellulose, residual alkali, etc. At present, papermaking black liquor is mainly discharged after treatment, or incinerated as fuel after concentration, or lignin is extracted by acidification precipitation, membrane separation, flocculation precipitation, etc. The obtained lignin is further used to prepare water-coal slurry additives, fertilizers and activated carbon, etc. Among them, the preparation of activated carbon requires carbonization, activation and other processes after the extraction of lignin. The above methods for treating or utilizing papermaking black liquor have problems such as high pollution, low resource utilization, complex operation and long process.
[0004] Spray pyrolysis is a powder material preparation method developed in recent years. After the precursor solution is atomized, a series of physical and chemical processes such as solvent evaporation, solid particle formation, particle drying, thermal decomposition, and sintering are instantly completed in the reactor to finally form ultrafine powder. The process is simple and the finished product can be obtained in one step.
[0005] This project aims to efficiently utilize high-molecular organic matter such as lignin and hemicellulose in papermaking black liquor, directly prepare high-capacity activated carbon materials through spray pyrolysis, and use the activated carbon as the positive electrode to develop lithium-ion capacitors with high energy density, thereby realizing short-process and high-value application of papermaking black liquor. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a short-process preparation of activated carbon material from concentrated papermaking black liquor, a production method thereof and a lithium ion capacitor using the activated carbon material, in response to the problems of lithium ion capacitor positive electrode material and papermaking black liquor treatment raised in the above background technology.
[0007] In order to solve the above technical problems, the technical solution provided by the present invention is: a positive electrode material for a lithium ion capacitor, wherein the positive electrode material is an activated carbon material, wherein the activated carbon material has a spherical porous structure, wherein some carbon spheres are collapsed, and the BET specific area is 300-1000m 2 / g, is a porous spherical material rich in mesoporous structure, the diameter of the spherical activated carbon is about 0.2-3um, the wall thickness is about 20-50nm, the (002) crystal plane interlayer spacing (d 002 ) is 0.36-0.37nm, and the average thickness along the c-axis direction (L c ) is 0.7-0.85nm, and the average width along the a-axis direction (L a ) is 9.5-12nm.
[0008] The method for preparing activated carbon material is as follows: papermaking black liquor is atomized, and an inert gas is used as a carrier gas. The atomized droplets enter an atmosphere protection furnace together with the inert gas, and the high-temperature pyrolysis of the black liquor and the activation and pore formation of the carbon material are completed in one step in the atmosphere protection furnace. The activated carbon material is obtained by collection, washing and drying.
[0009] As an improvement, the total dissolved solids (including lignin, hemicellulose and their derivatives, sodium salts, residual alkali, etc.) in the papermaking black liquor is 50-600 g / L, the total carbon content (TOC) is 10-100 g / L, and the hydroxide (OH - ) content is 2-30g / L, and the sodium (Na) content is 10-100g / L.
[0010] As an improvement, the collection is to introduce the pyrolyzed solid material and tail gas into a collector filled with a dilute sodium hydroxide solution.
[0011] As an improvement, the inert gas contains at least one of nitrogen and argon.
[0012] As an improvement, the water partial pressure in the atmosphere protection furnace is 0.4-0.7atm.
[0013] As an improvement, the temperature of the high temperature pyrolysis and activation pore formation is 600-720°C.
[0014] As an improvement, the atomization includes ultrasonic atomization and centrifugal atomization.
[0015] The activated carbon material is used as the positive electrode material, one or more of artificial graphite, graphitized mesophase carbon microspheres and hard carbon are used as the negative electrode material, the electrolyte is 1.3-1.5 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio is x:1-x, x=0.15-0.3) solution, and 5-15wt.% of ethyl acetate (EA) and 5-10wt.% of fluoroethylene carbonate (FEC), 1-1.5wt.% of biphenyl (BP) are added as additives to prepare a high-voltage lithium ion capacitor, which is charged and discharged between 2.0-4.0V and has an energy density of 110-124Wh·kg-1.
[0016] After adopting the above materials and preparation methods, the present invention has the following advantages: (1) The concentrated papermaking black liquor is prepared into activated carbon material through a short process of spray pyrolysis, which is used as the positive electrode material of the high-capacity lithium ion capacitor, thereby realizing efficient value-added of the papermaking black liquor.
[0017] (2) The spherical porous carbon material is obtained by the spray pyrolysis method. At the same time, the synergistic effect of the high content of water introduced during the spraying process, the sodium hydroxide in the papermaking black liquor and the sodium oxide produced by the decomposition of sodium salts, and the high temperature can be used to achieve carbonization and activation pore formation of the papermaking black liquor in one step during the high-temperature pyrolysis process.
[0018] (3) The solid material and tail gas after pyrolysis are introduced into a collector containing a dilute sodium hydroxide solution, thereby achieving the purposes of sealing the atmosphere protection furnace, collecting the porous carbon material, absorbing and treating the pyrolysis tail gas, and removing soluble impurities.
[0019] (4) The prepared activated carbon material has a spherical porous structure, and some carbon spheres are collapsed.
[0020] Shape, BET specific area is 300-1000m 2 / g, with an average pore size of 1.8-3nm. It is a porous spherical material rich in mesoporous structure. The diameter of spherical activated carbon is about 0.2-3um, the wall thickness is about 20-50nm, and the interlayer spacing is d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.7-0.85nm. a It is 9.5-12nm, which meets the high capacity requirements of activated carbon for lithium-ion capacitors.
[0021] (5) A porous spherical activated carbon with high capacity characteristics is used as the positive electrode material, and one or more of artificial graphite, graphitized mesophase carbon microspheres, and hard carbon are used as the negative electrode materials. The electrolyte is 1.3-1.5 mol / L LiPF6 EC / DMC (volume ratio is x:1-x, x=0.15-0.3) solution, and 5-15wt.% EA and 5-10wt.% FEC, 1-1.5wt.% BP (biphenyl) are added as additives to prepare a high-voltage lithium ion capacitor that can be charged and discharged in a wide voltage range (2.0-4.0V) and has a high energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The invention discloses a positive electrode material for a lithium ion capacitor and a preparation method thereof, and an SEM image of an activated carbon material for a lithium ion capacitor using the positive electrode material;
[0023] Figure 2The invention discloses a positive electrode material for a lithium ion capacitor and a preparation method thereof, and a SEM image of an activated carbon material for a lithium ion capacitor using the positive electrode material;
[0024] Figure 3 A positive electrode material for a lithium ion capacitor and a preparation method thereof, and a TEM image of an activated carbon material for a lithium ion capacitor using the positive electrode material;
[0025] Figure 4 The figure is a charge and discharge curve diagram of a lithium ion capacitor using this positive electrode material. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0027] Combined with Figure 1-4 A positive electrode material for a lithium ion capacitor, wherein the positive electrode material is an activated carbon material, wherein the activated carbon material has a spherical porous structure, wherein some carbon balls are collapsed, and the BET specific area is 300-1000m 2 / g, with an average pore size of 1.8-3nm, and is a porous spherical material rich in mesoporous structure. The diameter of the spherical activated carbon is about 0.2-3um, the wall thickness is about 20-50nm, and the (002) crystal plane interlayer spacing (d 002 ) is 0.36-0.37nm, and the average thickness along the c-axis direction (L c ) is 0.7-0.85nm, and the average width along the a-axis direction (L a ) is 9.5-12nm.
[0028] A preparation method of a positive electrode material for a lithium ion capacitor: papermaking black liquor is atomized, and an inert gas is used as a carrier gas. The atomized droplets enter an atmosphere protection furnace together with the inert gas, and the high-temperature pyrolysis of the black liquor and the activation and pore formation of the carbon material are completed in one step in the atmosphere protection furnace. The activated carbon material is obtained by collecting, washing, and drying. The total dissolved solids (including lignin, hemicellulose and their derivatives, sodium salts, residual alkali, etc.) in the papermaking black liquor are 50-600 g / L, the total carbon content (TOC) is 10-100 g / L, and the hydroxide (OH) - ) content is 2-30g / L, the sodium (Na) content is 10-100g / L, the collection is to introduce the pyrolyzed solid material and tail gas into a collector filled with a dilute sodium hydroxide solution, the inert gas contains at least one of nitrogen and argon, the water partial pressure in the atmosphere protection furnace is 0.4-0.7atm, the temperature of the high-temperature pyrolysis and activation pore formation is 600-720°C, and the atomization includes ultrasonic atomization and centrifugal atomization.
[0029] The activated carbon material is used as the positive electrode material, one or more of artificial graphite, graphitized mesophase carbon microspheres and hard carbon are used as the negative electrode material, the electrolyte is 1.3-1.5 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio is x:1-x, x=0.15-0.3) solution, and 5-15wt.% of ethyl acetate (EA) and 5-10wt.% of fluoroethylene carbonate (FEC), 1-1.5wt.% of biphenyl (BP) are added as additives to prepare a high-voltage lithium ion capacitor, which is charged and discharged between 2.0-4.0V and has an energy density of 110-124Wh·kg-1.
[0030] Specific Example 1: Papermaking black liquor (total dissolved solids 62 g / L, TOC 10.6 g / L, OH - 2.8g / L, Na10.4g / L) were ultrasonically atomized, and nitrogen was used as the carrier gas. The atomized droplets and nitrogen (3L / min) entered the atmosphere protection furnace together. H2O =0.45atm) at 700°C to complete the high-temperature pyrolysis of the black liquor and the activation and pore formation of the carbon material in one step, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, the activated carbon material is filtered, washed and dried to obtain the activated carbon material.
[0031] The obtained activated carbon material has a spherical porous structure, some carbon spheres are collapsed, and the BET specific area is 345.8m 2 / g, with an average pore size of 1.9nm. It is a porous spherical material rich in mesoporous structure. The diameter of spherical activated carbon is about 0.2-3um, the wall thickness is about 20-50nm, and the interlayer spacing is d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.81 nm. a The obtained activated carbon was used as the positive electrode material, assembled into a button cell with a metal lithium sheet, a separator and an electrolyte, and charged and discharged at a current density of 50 mA / g between 2-4 V, with a reversible capacity of 60.8 mAh / g (109.4 F / g).
[0032] For comparison, Kuraray YP50 was used as the positive electrode material, assembled into a button cell and charged and discharged in the same way, and the reversible capacity was 50 mAh / g (90 F / g).
[0033] The activated carbon material prepared in this embodiment is used as the positive electrode material of the lithium capacitor, and the lithium capacitor assembled with artificial graphite as the negative electrode material (the mass ratio of positive and negative active materials is 2:1), the electrolyte is 1.4mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio is x:1-x, x=0.25) solution, and 10wt.% of ethyl acetate (EA) and 7wt.% of fluoroethylene carbonate (FEC), 1.2wt.% biphenyl (BP) as additives are added to prepare a high-voltage lithium ion capacitor, which is charged and discharged between 2.0-4.0V, and the energy density is 110Wh·kg -1 (The total mass is the sum of the masses of the positive and negative electrode active materials).
[0034] Specific Example 2: Papermaking black liquor (total dissolved solids 62 g / L, TOC 10.6 g / L, OH - 2.8g / L, Na10.4g / L) were ultrasonically atomized, and nitrogen was used as the carrier gas. The atomized droplets and nitrogen (2L / min) entered the atmosphere protection furnace together. H2O =0.7atm) at 600°C to complete the high-temperature pyrolysis of the black liquor and the activation and pore formation of the carbon material in one step, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, the activated carbon material is filtered, washed and dried to obtain the activated carbon material.
[0035] The obtained activated carbon material has a spherical porous structure, some carbon spheres are collapsed, and the BET specific area is 305m 2 / g, with an average pore size of 3nm. It is a porous spherical material rich in mesoporous structure. The diameter of spherical activated carbon is about 0.2-3um, the wall thickness is about 20-50nm, and the interlayer spacing is d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.71 nm. a The obtained activated carbon was used as the positive electrode material, assembled into a button cell with a metal lithium sheet, a separator and an electrolyte, and charged and discharged at a current density of 50 mA / g between 2-4 V, with a reversible capacity of 60.1 mAh / g (108.2 F / g).
[0036] The activated carbon material prepared in this example is used as the positive electrode material of the lithium capacitor, and the graphitized mesophase carbon microspheres are used as the negative electrode material to assemble the lithium capacitor (the mass ratio of the positive and negative active materials is 2.5:1).
[0037] The electrolyte is 1.5 mol / L LiPF6 in ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio x:1-x, x=0.3) solution, and 15 wt.% ethyl acetate (EA) and 5 wt.% fluoroethylene carbonate (FEC), 1 wt.% biphenyl (BP) are added as additives to prepare a high-voltage lithium ion capacitor, which is charged and discharged between 2.0-4.0 V and has an energy density of 115 Wh kg -1 (The total mass is the sum of the masses of the positive and negative electrode active materials).
[0038] Specific Example 3: Papermaking black liquor (total dissolved solids 580 g / L, TOC 98 g / L, OH - 28g / L, Na95g / L) were centrifugally atomized, and nitrogen was used as the carrier gas. The atomized droplets and nitrogen (10L / min) entered the atmosphere protection furnace together. H2O =0.4atm) at 720°C to complete the high-temperature pyrolysis of the black liquor and the activation and pore formation of the carbon material in one step, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, the activated carbon material is filtered, washed and dried to obtain the activated carbon material.
[0039] The obtained activated carbon material has a spherical porous structure, some carbon spheres are collapsed, and the BET specific area is 980m 2 / g, with an average pore size of 1.8nm. It is a porous spherical material rich in mesoporous structure. The diameter of spherical activated carbon is about 0.2-3um, the wall thickness is about 20-50nm, and the interlayer spacing is d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.84 nm. a The activated carbon was used as the positive electrode material, assembled into a button cell with a metal lithium sheet, a separator and an electrolyte, and charged and discharged at a current density of 50 mA / g between 2-4 V, with a reversible capacity of 62.5 mAh / g (112.5 F / g).
[0040] The activated carbon material prepared in this embodiment is used as the positive electrode material of the lithium capacitor, and the lithium capacitor assembled with hard carbon as the negative electrode material (the mass ratio of positive and negative active materials is 3:1), the electrolyte is 1.3 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio is x:1-x, x=0.15) solution, and 5wt.% ethyl acetate (EA) and 10wt.% fluoroethylene carbonate (FEC), 1.5wt.% biphenyl (BP) are added as additives to prepare a high-voltage lithium ion capacitor, which is charged and discharged between 2.0-4.0V, and the maximum energy density is 124Wh·kg -1(The total mass is the sum of the masses of the positive and negative electrode active materials).
[0041] Specific Example 4: Papermaking black liquor (total dissolved solids 124 g / L, TOC 21.3 g / L, OH - 5.5g / L, Na20.8g / L) were ultrasonically atomized, and nitrogen was used as the carrier gas. The atomized droplets and nitrogen (4L / min) entered the atmosphere protection furnace together. H2O =0.4atm) at 650°C to complete the high-temperature pyrolysis of black liquor and the activation and pore formation of carbon materials in one step, and the obtained carbon material and tail gas are introduced into a collector filled with a dilute sodium hydroxide solution. After the spray pyrolysis is completed, the activated carbon material is filtered, washed and dried to obtain the activated carbon material.
[0042] The obtained activated carbon material has a spherical porous structure, some carbon spheres are collapsed, and the BET specific area is 482m 2 / g, with an average pore size of 2.5nm. It is a porous spherical material rich in mesoporous structure. The diameter of spherical activated carbon is about 0.2-3um, the wall thickness is about 20-50nm, and the interlayer spacing is d 002 The average thickness along the c-axis is L c The average width L along the a-axis is 0.77 nm. a The obtained activated carbon was used as the positive electrode material, assembled into a button cell with a metal lithium sheet, a separator and an electrolyte, and charged and discharged at a current density of 50 mA / g between 2-4 V, with a reversible capacity of 62.8 mAh / g (113.0 F / g).
[0043] The activated carbon material prepared in this embodiment is used as the positive electrode material of the lithium capacitor, and the graphitized mesophase carbon microspheres are used as the negative electrode material to assemble the lithium capacitor (the mass ratio of the positive and negative active materials is 2:1), the electrolyte is 1.35mol / LLiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio is x:1-x, x=0.2) solution, and 10wt.% of ethyl acetate (EA) and 8wt.% of fluoroethylene carbonate (FEC), 1.25wt.% biphenyl (BP) as additives are added to prepare a high-voltage lithium ion capacitor, which is charged and discharged between 2.0-4.0V, and the maximum energy density is 113Wh·kg -1 (The total mass is the sum of the masses of the positive and negative electrode active materials).
[0044] The present invention and its implementation methods are described above, and such description is not restrictive, and the actual structure is not limited thereto. In short, if a person skilled in the art is inspired by it, and does not deviate from the purpose of the invention, and does not creatively design a structure and implementation method similar to the technical solution, they should all fall within the protection scope of the present invention.
Claims
1. A positive electrode material for a lithium ion capacitor, characterized in that: The positive electrode material is an activated carbon material, which has a spherical porous structure, some carbon balls are collapsed, and the BET specific area is 300-1000m 2 / g, with an average pore size of 1.8-3nm, and is a porous spherical material rich in mesoporous structure. The diameter of the spherical activated carbon is about 0.2-3um, the wall thickness is about 20-50nm, and the (002) crystal plane interlayer spacing (d 002 ) is 0.36-0.37nm, and the average thickness along the c-axis direction (L c ) is 0.7-0.85nm, and the average width along the a-axis direction (L a ) is 9.5-12nm.
2. The method for preparing a negative electrode material for a lithium ion capacitor according to claim 1, characterized in that: The papermaking black liquor is atomized, and an inert gas is used as a carrier gas. The atomized droplets enter the atmosphere protection furnace together with the inert gas. The high-temperature pyrolysis of the black liquor and the activation and pore formation of the carbon material are completed in one step in the atmosphere protection furnace. The activated carbon material is obtained by collection, washing and drying.
3. The method for preparing a negative electrode material for a lithium ion capacitor according to claim 2, characterized in that: The total dissolved solids (including lignin, hemicellulose and their derivatives, sodium salt, residual alkali, etc.) in the papermaking black liquor are 50-600 g / L, the total carbon content (TOC) is 10-100 g / L, and the hydroxide (OH) - ) content is 2-30g / L, and the sodium (Na) content is 10-100g / L.
4. The method for preparing a negative electrode material for a lithium ion capacitor according to claim 2, characterized in that: The collection is to introduce the pyrolyzed solid materials and tail gas into a collector filled with a dilute sodium hydroxide solution.
5. The method for preparing a negative electrode material for a lithium ion capacitor according to claim 2, characterized in that: The inert gas contains at least one of nitrogen and argon.
6. The method for preparing a negative electrode material for a lithium ion capacitor according to claim 2, characterized in that: The water partial pressure in the atmosphere protection furnace is 0.4-0.7atm.
7. The method for preparing a negative electrode material for a lithium ion capacitor according to claim 2, characterized in that: The temperature of the high temperature pyrolysis and activation pore formation is 600-720°C.
8. The method for preparing a negative electrode material for a lithium ion capacitor according to claim 2, characterized in that: The atomization includes ultrasonic atomization and centrifugal atomization.
9. A lithium ion capacitor using the lithium ion capacitor negative electrode material according to claim 1, characterized in that: The activated carbon material according to claim 1 is used as the positive electrode material, one or more of artificial graphite, graphitized mesophase carbon microspheres, and hard carbon are used as the negative electrode material, the electrolyte is 1.3-1.5 mol / L LiPF6 ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio is x:1-x, x=0.15-0.3) solution, and 5-15wt.% of ethyl acetate (EA) and 5-10wt.% of fluoroethylene carbonate (FEC), 1-1.5wt.% of biphenyl (BP) are added as additives to prepare a high-voltage lithium ion capacitor, which is charged and discharged between 2.0-4.0V and has an energy density of 110-124Wh·kg -1 .
Citation Information
Patent Citations
Preparation of natural nutshell carbon material and application of natural nutshell carbon material in electrochemical capacitors
CN104064369A
Lithium ion capacitor and preparation method thereof
CN111435632A
Capacitor, method of controlling the same, and transistor including the same
KR1020210138997A